2020
DOI: 10.3390/cells9040856
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Extracellular Vesicle Promotes Hair Growth

Abstract: Hair loss is a common medical problem affecting both males and females. Dermal papilla (DP) cells are the ultimate reservoir of cells with the potential of hair regeneration in hair loss patients. Here, we analyzed the role of macrophage-derived Wnts (3a and 7b) and macrophage extracellular vesicles (MAC-EVs) in promoting hair growth. We studied the proliferation, migration, and expression of growth factors of human-DP cells in the presence or absence of MAC-EVs. Additionally, we tested the effect of MAC-EV tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 72 publications
8
58
0
Order By: Relevance
“…Moreover, intradermal injection of Wnt3a- and Wnt7b-enriched MAC-EV in male balb/C mice enhanced HF growth in vivo. Moreover, treatment with MAC-EV increased the size of hair shaft in human HF in a short time period [ 48 ]. Conversely, Wnt5a, a non-canonical Wnt expressed in bulge and secondary hair germ cells at telogen stage, antagonizes the function of canonical Wnts.…”
Section: Role Of Wnt/β-catenin Signaling In Hair Growthmentioning
confidence: 99%
“…Moreover, intradermal injection of Wnt3a- and Wnt7b-enriched MAC-EV in male balb/C mice enhanced HF growth in vivo. Moreover, treatment with MAC-EV increased the size of hair shaft in human HF in a short time period [ 48 ]. Conversely, Wnt5a, a non-canonical Wnt expressed in bulge and secondary hair germ cells at telogen stage, antagonizes the function of canonical Wnts.…”
Section: Role Of Wnt/β-catenin Signaling In Hair Growthmentioning
confidence: 99%
“…It was also shown that macrophage-EVs were enriched in the active accessible pool of cholesterol, which increased the efficiency of cholesterol transfer to high-density lipoprotein, thus lowering the cholesterol level 63 . A recent study reported that Wnt proteins, such as Wnt3a and Wnt7b, were enriched in macrophage-EVs, thus activating the Wnt/β-catenin signaling pathway to enhance hair follicle growth in vivo and in vitro 64 .…”
Section: Characteristics and Functions Of Evs From Cells Associated Wmentioning
confidence: 99%
“…Moreover, experiments in the culture of mouse macrophages showed that their apoptosis occurs in parallel with the release of Wnts and that apoptotic macrophages stimulate the expression of Wnts by neighboring macrophages (Castellana et al, 2014). Interestingly, macrophages seem to produce extracellular vesicles containing Wnt3a and Wnt7b (Rajendran et al, 2020). Thus, the apoptotic reduction of macrophages during TAT is associated with the activation of the Wnt/β-catenin cascade (Castellana et al, 2014).…”
Section: The Hf Cycle and Immunity In Physiological And Injury-inducementioning
confidence: 99%